Biocatalytic approach for the utilization of hemicellulose for ethanol production from agricultural residue using thermostable xylanase and thermotolerant yeast - Menon, Vishnu; Prakash, Gyan; Prabhune, Asmita; Rao, Mala (Bioresource Technology, 2010)
A hydrolysis of 62% and 50% for OSX (Oat spelt xylan) and WBH (Wheat bran hemicellulose) were obtained in 36 h and 48 h using Accellerase(TM) 1000 at 50 degrees C wherein thermostable xylanase from alkalothermophilic Thermomonospora sp. yielded 67% (OSX) in 3 h and 58% (WBH) in 24 h at 60 degrees C, favouring a reduction in process time and enzyme dosage. The rate of hydrolysis with thermostable xylanase was increased by 20% with the addition of nonionic surfactant tween 80 or biosurfactant sophorolipid. The simultaneous saccharification and fermentation (SSF) of OSX and WBH using thermostable xylanase and D. hansenii in batch cultures produced 9.1 g/L and 9.5 g/L of ethanol, respectively and had a shorter overall process time than the separate hydrolysis and fermentation (SHF). The immobilized yeast cells in Ca-alginate matrix produced ethanol with a yield of 0.46 g/g from hemicellulosic hydrolysates and were reused six times with 100% fermentation efficiency. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biosurfactant; Ethanol; Hemicellulose; Thermostable xylanase; Thermotolerant yeast

Bioethanol production from renewable polymer lichenan using lichenase from an alkalothermophilic thermomonospora sp and thermotolerant yeast - Menon, Vishnu; Divate, Rupesh; Rao, Mala (Fuel Processing Technology, 2011)
Biomass feedstocks available decentrally will be more commodious for localized biorefinery approach than the exhaustive large scale and centralized plants driven by cost intensive technology. Lichen is present in a wide range of habitats in a distributed manner. A maximum hydrolysis of 73%-76% for lichenan from Cetraria islandica, Usnea barbata and Parmelia sp. were obtained in 24 h using lichenase from an alkalothermophilic Thermomonospora sp. wherein the hydrolysis was 100% with commercial enzyme Accellerase (TM) 1000. The synergistic role of beta-glucosidase in lichenan hydrolysis was demonstrated by the exogenous addition of beta-glucosidase to Thermomonospora lichenase which resulted in complete hydrolysis. The hydrolysates of lichenan obtained using Accellerase or a cocktail of Thermomonospora lichenase and beta-glucosidase when fermented with free cells of Saccharomyces at 40 degrees C produced an ethanol yield of 0.45 g/g-0.48 g/g with theoretical conversion efficiencies of 93%-96%. The Ca-alginate immobilized yeast cells were reused eight times at 40 degrees C with 100% fermentation efficiency. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Hydrolysis; Lichenan; Lichenase; Synergism; Thermotolerant yeast

Biochemical characterization of a novel thermostable xyloglucanase from an alkalothermophilic thermomonospora sp. - Pol, Dipali; Menon, Vishnu; Rao, Mala (Extremophiles, 2012)
Xyloglucanase from an extracellular culture filtrate of alkalothermophilic Thermomonospora sp. was purified to homogeneity with a molecular weight of 144 kDa as determined by SDS-PAGE and exhibited specificity towards xyloglucan with apparent K (m) of 1.67 mg/ml. The enzyme was active at a broad range of pH (5-8) and temperatures (40-80A degrees C). The optimum pH and temperature were 7 and 70A degrees C, respectively. The enzyme retained 100% activity at 50A degrees C for 60 h with half-lives of 14 h, 6 h and 7 min at 60, 70 and 80A degrees C, respectively. The kinetics of thermal denaturation revealed that the inactivation at 80A degrees C is due to unfolding of the enzyme as evidenced by the distinct red shift in the wavelength maximum of the fluorescence profile. Xyloglucanase activity was positively modulated in the presence of Zn2+, K+, cysteine, beta-mercaptoethanol and polyols. Thermostability was enhanced in the presence of additives (polyols and glycine) at 80A degrees C. A hydrolysis of 55% for galactoxyloglucan (GXG) from tamarind kernel powder (TKP) was obtained in 12 h at 60A degrees C and 6 h at 70A degrees C using thermostable xyloglucanases, favouring a reduction in process time and enzyme dosage. The enzyme was stable in the presence of commercial detergents (Ariel), indicating its potential as an additive to laundry detergents.
Keywords: Alkalothermophilic Thermomonospora sp.; Biotechnological applications; Purification; Thermostable; Xyloglucanase